Theoretical Study of the Pt/TiO2 Interface in Photocatalytic Systems - Thaines, Ericson Hamissés Nunes Souza (2024)
The present work presents a study of the structural and electronic properties of TiO 2, Fe-doped TiO2, Pt(1 1 1)/TiO2(hkl) interface, and Pt3(1 1 1)/TiO2(hkl) interface, probing the photocatalytic properties from a theoretical approach. The study of the materials starts with characterization by X-ray diffraction, where peaks related to the phases TiO2-anatase, TiO2 - rutile, and Pt were indexed. Anatase and rutile phases of TiO2 doped with Fe, Pt(1 1 1)/TiO2(hkl) interface, and Pt3(1 1 1)/TiO2 (hkl) interface were investigated using both experimental and theoretical approaches, and the phases were characterized by X-ray diffraction with Rietveld refinement. Electronic properties were characterized using DFT/plane-wave calculations. Water splitting reaction on anatase surfaces (0 1 0) TiO2 and TiO2-Fe was investigated. Activation energies of 0.29 eV and 0.08 eV were estimated for pure anatase TiO2 and anatase TiO2-F e structures. From Rietveld refinement, deformations in the crystal lattice of the phases were analyzed using µstrain analysis, where it is observed that the anatase TiO2 phase undergoes greater deformation compared to the Pt phase, as can be seen in the calculated values of bulk modulus (B0), since B0−Pt > B0−TiO2 . Material simulation was carried out using the crystallographic parameters obtained previously with Rietveld refinement. The study of the Pt(1 1 1)/TiO2(h k l) interface was conducted considering two planes of the TiO2 phase, (1 0 1) and (0 0 1), which were observed in the Rietveld refinement. From the analysis of interface PDOS, a new electronic state between the valence band and conduction band of the TiO2 phase, attributed to the Pt phase, was observed. Theoretical modeling of the Pt3(1 1 1)/TiO2(h k l) interface considering approximately 60% of the TiO2 phase and 40% of the Pt phase determined in the Rietveld refinement. The Pt3(1 1 1)/TiO2(1 0 1) interface showed the lowest activation energy for hydrogen molecule splitting of 0.19 eV with exothermic character. For water splitting, both interfaces Pt3(1 1 1)/TiO2 (h k l) presented the same activation energy ∼ 1.4 eV with endothermic character.